Is independence really a requirement for members of the bodies with control functions in Italian banking?. (2017) - Giovanelli, Lucia; Rotondo, Federico
This paper aims to shed light on the quality of the independent members of governance bodies charged with the oversight of organisations' audit and control functions. A biographical investigation is carried out into the 118 independent members of the bodies with control functions of the Italian banks that underwent comprehensive assessment by the European Central Bank (ECB). An identikit comes to light of a man almost 60 years of age, coming from the banking regions, who graduated in the field of economics and is highly experienced. A sufficient degree of diversity among members is found in relation to age and provenance, while serious concerns are raised about their time availability and true independence. This paper advances the understanding of the importance of personal qualities in corporate governance studies and provides support for theories stating that the quality of people matters more than requirements and guidelines for reducing agency costs.